GEOLOGY OF THE USA CRREL PERMAFROST TUNNEL, FAIRBANKS, ALASKA - Sellmann, Paul V. (1967)
The study provides the pertinent regional and historical geology of the tunnel site and immediate surroundings as well as data on the index properties and seismic velocities of the material through which the tunnel passes. The tunnel, located in the discontinuous permafrost zone, is discussed with emphasis on bedrock, gravel, silt, ground ice, and chemical gradient. A study of the stratigraphy of the section reveals a record of the past climatic history of the area, based on the structure and distribution of the ice wedges, chemical gradients, sedimentary structures, radiocarbon dates, and the lithology of the material exposed along the tunnel section and vertical ventilation shaft. Two recognizable unconformities appear in the section. The large size of the wedges suggests that depositional rates were fairly slow during the period of wedge development. It can also be concluded that within the last 30,000 yr a minimum of 30 ft of silt was deposited, most of which is Wisconsin age.